The Economic Impact of the COVID-19 Pandemic on France and South Korea - Cjura, Jana (2022)
This thesis deals with the effects of the covid-19 pandemic on the economies of France and South Korea between 2020 and 2021, as both countries have chosen different approaches to this crisis. The thesis hypothesizes that the French economy has managed the coronavirus pandemic worse than South Korea. The main goal is to evaluate the economic impacts of the pandemic and the effectiveness of the applied measures taken in both countries. The thesis is divided into four chapters, the first of which deals with the characterization of the coronavirus pandemic in general. The second chapter analyzes how the evaluated countries were prepared for such a crisis, how the disease spread, and what measures these countries used. The third chapter deals with the evaluation of the performance of both economies using magic squares and other macroeconomic indicators in the period 2019-2021. The last chapter compares the approaches of both countries and finds out whether it is possible to apply some aspects of South Korea’s success in France, as another goal of this thesis is to propose possible solutions to France's economic problems after 2021.